2006
DOI: 10.1021/la053395e
|View full text |Cite
|
Sign up to set email alerts
|

Particle Growth of Hybrid Materials Followed by Dynamic Light Scattering

Abstract: The hydrolysis of distannylated compounds in which the tin atoms are linked by an organic spacer has been studied under microemulsion conditions using dynamic light scattering and infrared spectroscopy. The experiments provided evidence that the growth of hybrid material particles occurs in the aqueous phase, outside the organic phase of the microemulsion. The growth rates of the particles were found to be strongly dependent on the nature of the spacers, a polymethylene chain inducing the fastest process. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Bridged precursors of silsesquioxanes X 3 Si-R′-SiX 3 or more recently bridged stananes X 3 Sn-R′-SnX 3 (R′ is an organic spacer, X = Cl, Br, −OR) have opened a plethora of new possibilities for the controlled design of hybrid POMMs (path A-3). , Indeed, under surfactant directed assembly conditions, their condensation (path A-3) or co-condensation with metal alkoxides or organically modified alkoxysilanes (path A-3 with association of molecular precursors of path A-1 or A-2) allows the selective placement of different organic functionalities inside the pores, walls, or both via a convenient one pot synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Bridged precursors of silsesquioxanes X 3 Si-R′-SiX 3 or more recently bridged stananes X 3 Sn-R′-SnX 3 (R′ is an organic spacer, X = Cl, Br, −OR) have opened a plethora of new possibilities for the controlled design of hybrid POMMs (path A-3). , Indeed, under surfactant directed assembly conditions, their condensation (path A-3) or co-condensation with metal alkoxides or organically modified alkoxysilanes (path A-3 with association of molecular precursors of path A-1 or A-2) allows the selective placement of different organic functionalities inside the pores, walls, or both via a convenient one pot synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 16 − 22 were subsequently hydrolyzed in THF, yielding transparent or opaque gels, depending on the hydrolysis conditions, which were then thermolyzed, forming high surface area mesoporous tin oxide …”
Section: Resultsmentioning
confidence: 99%
“…1,3-Dihydro-1,3-dioxa-2,4-distannetanes are usually prepared in two different ways, either by hydrolysis of tin halides or by condensation between a tin oxide or hydroxide and an acid, often under Dean-Stark conditions. During the course of our studies concerning the hydrolysis of organotrialkynyltins [21][22][23][24][25] and bridged organohexaalkynylditins [26][27][28][29] we showed that the use of a bulky substituent on the tin, such as the 2,4,6-trii-propylphenyl group, could allow the isolation of clusters of monoorganotin oxides-hydroxides of various sizes and shapes. When hydrolysis was conducted in the presence of an aromatic sulfonic acid, cationic polysulfonates with three or ten tin atoms and two types of sulfonate bondings, an electrostatic and a bridging one, were isolated [22].…”
Section: Introductionmentioning
confidence: 99%